2021
DOI: 10.3390/molecules26051217
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Phytochemical Properties, Antioxidant Activity and Cytotoxic Effect on HepG2 Cells in Mongolian and Taiwanese Rhubarb Species

Abstract: The Mongolian rhubarb—Rheum undulatum L. (RU)—and Rumex crispus L. (RC)—a Taiwanese local rhubarb belonging to the family of Polygonaceae—are principal therapeutic materials in integrative medicine due to their rich quantities of bioactive compounds; however, their phytochemical and antioxidant properties, and anti-cancer activity is poorly investigated. Furthermore, the phytochemical characteristics of both species may be affected by their different geographical distribution and climatic variance. The current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…The cytotoxic activity of ethyl acetate extract against PANC-1 cell was in correlation with phytochemical content (−0.994). This is indicating that phytochemical content could play a key role against these cancer cell line due to their ability to remove reactive oxygen species which cause cell damage [38], [39], [40]. According to these results, the varied cytotoxic activity of extracts may be attributed to the difference in the concentration of phenolic and flavonoid compounds in each extracts.…”
Section: Discussionmentioning
confidence: 81%
“…The cytotoxic activity of ethyl acetate extract against PANC-1 cell was in correlation with phytochemical content (−0.994). This is indicating that phytochemical content could play a key role against these cancer cell line due to their ability to remove reactive oxygen species which cause cell damage [38], [39], [40]. According to these results, the varied cytotoxic activity of extracts may be attributed to the difference in the concentration of phenolic and flavonoid compounds in each extracts.…”
Section: Discussionmentioning
confidence: 81%
“…Rhei Undulati Rhizoma (RUR), an herbal medicine belonging to the family Polygonaceae, have traditionally been used to treat constipation, ulcers, and jaundice in the East Asia [ 18 ]. Furthermore, recent studies have reported that RUR has various pharmacological activities such as anti-inflammatory, antioxidant, and anti-neuroinflammatory effects [ 19 21 ]. Furthermore, rhapontigenin in stilbene glucosides isolated from RUR has a neuroprotective effect against Aβ-induced neurotoxicity [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In the clinical treatment of Chinese medicine, the main extraction method of RT was water decoction, but modern pharmacological activity studies have reported that some extraction of RT with ethanol has a better effect than water decoction. [4][5][6] In the research model of plant metabolomics, based on a multivariate statistical analysis platform, high-throughput screening of components with significant differences provides a robust technology for studying the material basis between different extraction methods of RT.…”
Section: Introductionmentioning
confidence: 99%